GERAKAN LITERASI SEKOLAH DALAM PENINGKATAN PRESTASI BELAJAR SEJARAH KEBUDAYAAN ISLAM (SKI) SISWA MAN 4 AGAM - Donny Firdaus; Salmi Wati; Zulfani Sesmiarni; Wedra Aprison (Universitas Pahlawan Tuanku Tambusai, 2022)
This writing is motivated by the declining learning achievement of students at MAN 4 Agam due to the laziness of students to read, write, understand, and communicate the knowledge they have learned, which causes students' grades to decline. Because the development of the era of students more and more misuse the internet. It would be nice to use the internet for learning such as reading, listening or watching shows that contain education. So to overcome this and revive reading culture, the government made regulation No.23 of 2015, the Ministry of Culture and Education requires reading books 15 minutes before learning. Also known as the School Literacy Movement. For this reason, the author tries to describe the School Literacy Movement at MAN 4 Agam in increasing learning achievement of Islamic Cultural History. The type of research that the researcher uses in this research is Field Research. While the research method that the author uses is descriptive qualitative, namely research that describes the data as it is in the field. In this study, the author describes the implementation of the School Literacy Movement at MAN 4 Agam. The data collection method was taken from observation, documentation and interviews with key informants and supporting informants. Based on the results of the research, it can be concluded that the Literacy Movement is very effective in improving the ability to read, write, understand and communicate again. Which will later improve student learning achievement itself. As in the research of researchers, namely the learning of Islamic Cultural History which makes learning outcomes satisfying. There are three stages of the School Literacy Movement activity, namely the habituation stage, the development stage and the literacy stage in learning. The MAN 4 religious school itself has carried out these three stages and is still running at the literacy stage in learning. Keyword: School Literacy Movement, Learning Achievement, Islamic Cultural History Learning